Subjective Well-being in Retirement: Evidence from HILDA - Barrett, G (My University, 2011)
Does retirement represent a state of relative prosperity or a time of unanticipated economic hardship? To address the question of whether individuals are successful in smoothing their wellbeing across the transition to retirement we analyse measures of subjective wellbeing (SWB) in the HILDA Survey. Specifically, this research examines individual's self-reported changes in standard of living, financial security, and overall happiness over the transition to retirement. It is found SWB either improves or remains constant for the large majority of individuals as retire from the labour force. However, there are significant disparities in changes in well-being with retirement. In particular, the subset of individuals who are forced to retire early due to job loss or their own health, and who find their income in retirement is much less than expected, report marked declines in their well-being in retirement. This research also makes a methodological contribution by examining the accuracy of relative SWB measures. For the subset of individuals who retire after 2001, we use the longitudinal information in HILDA to assess the reliability of the retrospective reports of changes in SWB with contemporaneous responses.
Keywords: Health -- Wellbeing; Health; Finance; Ageing; Ageing -- Retirement; Health and wellbeing; Ageing; Income, wealth and finances; Ageing; Health; Finance; Wellbeing; Retirement; Ageing; Health and wellbeing; Income, wealth and finance